785 Sodium–glucose cotransporter 2 inhibitors in real-life patients at high cardiovascular risk. (8th December 2021) - Cesaro, Arturo; Fimiani, Fabio; Gragnano, Felice; Moscarella, Elisabetta; Signore, Giovanni; Maratea, Anna Chiara; Rotolo, Francesco Paolo; Vergara, Andrea; Schiavo, Alessandra; Calabrò, Paolo
Abstract: Sodium-glucose cotransporter 2 inhibitors (SGLT2i), were recently approved in the USA and the EU for the treatment of adults with symptomatic heart failure with reduced ejection fraction (HFrEF). These drugs currently play a prominent role in the treatment algorithm for HFrEF [ejection fraction ≤40%], and international guidelines considered they as first-line drugs. However, data on the use of SGLT2i in real-world practice lack. We aim at providing data on SGLT2i in high cardiovascular risk patients in the real-world setting. We have retrospectively evaluated high cardiovascular risk patients treated with SGLT2i according to Italian national regulation, and collected 1-year outcomes. The primary objective of the study is to generate real-world data about clinical characteristics, major adverse cardiovascular events (MACE), hospitalizations for heart failure, and adverse event in patients receiving canagliflozin, empagliflozin, dapagliflozin, ertugliflozin from our cohort. Ninety-three patients with diabetes treated with SGLT2i were retrospectively enrolled. At 1-year follow-up, the rate of hospitalization was 10.7%, the MACE events occurred in 6.4% of patients; of these, 4.3% had a myocardial infarction, and 2.1% had a stroke/TIA, the rate of urinary tract infections was 5.3% while no major adverse event occurred. In conclusion, in a real-world study including patients with high and very high cardiovascular risk, SGLT2i showed to be safe, with no major adverse events occurring at follow-up.